Phenotypic variation and vocal divergence reveals a species complex in White-eared Ground-sparrows (Cabanis) (Aves: Passerellidae) - Sandoval, Luis; Bitton, Pierre-Paul; Demko, Alana D.; Doucet, Stéphanie M.; Mennill, Daniel J. (Zootaxa, 2017)
The taxonomy of the genus Melozone has recently been analyzed from genus to subspecies level, leading to a significant revision of our understanding of this group of birds. Previous studies quantified differences in phenotypic traits, behavior, and genotypes, to provide a better understanding of the underappreciated diversity within Melozone and the relationship between species within this genus. Yet the relationship between the subspecies of White-eared Ground-sparrows, Melozone leucotis, has not received thorough taxonomic scrutiny. In this study, we evaluate the taxonomic status of the three recognized subspecies of M. leucotis using multiple morphometric characteristics, plumage color features, and vocalizations. We measured plumage patterns and reflectance from museum specimens, morphometric features from museum specimens and live birds, and vocal characteristics from sound recordings. We observed substantial variation between subspecies in plumage, morphometry, and voice, especially between northern and southern birds. The phenotypic and vocal differences exhibited by M. l. occipitalis (from Chiapas, Mexico; Guatemala; and El Salvador) suggest that its taxonomic relationship with the M. l. leucotis and M. l. nigrior complex (from Costa Rica and Nicaragua, respectively) needs to be reevaluated, because these two groups are highly diagnosable from one another. Additionally, M. l. occipitalis is geographically isolated from the other two subspecies, reducing the probability of contact by natural causes in the near future. Based on the clear differences in voice, plumage, and morphometric features reported here, we propose that M. l. occipitalis be recognized as a distinct species, M. occipitalis (Salvin’s Ground-sparrow), diagnosed on the basis of its longer tail, longer bill, duller plumage, and songs with a lower frequency of maximum amplitude.